4-Chlorophenol Oxidation Depends on the Activation of an AraC-Type Transcriptional Regulator, CphR, in Rhodococcus sp. Strain YH-5B - Zhang, Hui; Yu, Ting; Wang, Yiran; Li, Jie; Wang, Guangli; Ma, Yingqun; Liu, Yu (Frontiers in Microbiology, 2018)
4-Chlorophenol (4-CP) oxidation plays an essential role in the detoxification of 4-CP. However, oxidative regulation of 4-CP at the genetic and biochemical levels has not yet been studied. To explore the regulation mechanism of 4-CP oxidation, a novel gene cluster, cphRA2A1, involved in biodegradation of 4-CP was identified and cloned from Rhodococcus sp. strain YH-5B by genome walking. The sequence analysis showed that the cphRA2A1 gene cluster encoded an AraC-type transcriptional regulator and a two-component monooxygenase enzyme, while quantitative real-time PCR analysis further revealed that cphR was constitutively expressed and positively regulated the transcription of cphA2A1 genes in response to 4-CP or phenol, as evidenced by gene knockout and complementation experiments. Through the transcriptional fusion of the mutated cphA2A1 promoter with the lacZ gene, it was found that the CphR regulator binding sites had two 15-bp imperfect direct repeats (TGCA-N6-GGNTA) at -35 to -69 upstream of the cphA2A1 transcriptional start site. Notably, the sub-motifs at the -46 to -49 positions played a critical role in the appropriate interaction with the CphR dimer. In addition, it was confirmed that the monooxygenase subunits CphA1 and CphA2, which were purified by His-tag affinity chromatography, were able to catalyze the conversion of 4-CP to 4-chlorocatechol, suggesting that strain YH-5B could degrade 4-CP via the 4-chlorocatechol pathway. This study enhances our understanding of the genetic and biochemical diversity in the transcriptional regulation of 4-CP oxidation in Gram-positive bacteria.